The Influence Of Brand Image, Product Quality, and Price On Purchasing Decision Of Le Minerale Brand Mineral Water in Nusantara PGRI Kediri University Students - Putri Wulandari, Nabela; Kurniawan, Rony (Universitas Nusantara PGRI Kediri, 2025)
Aim of research: This research seeks to determine the influence of brand image, product quality, and price on purchasing decision for Le Minerale Brand Mineral Water among students at Nusantara PGRI University, Kediri. Design/Methode/Approach : This research employs a quantitative methodology utilizing causative research techniques. The target population comprises students from the Economics and Business Faculty at Universitas Nusantara PGRI Kediri, specifically those from the 2021 cohort totaling of 455 students . A non-probability sampling method was implemented, selecting 40 respondents through purposive sampling. Data collection involved the distribution of questionnaires that had undergone validity and reliability testing prior to dissemination. The questionnaires were distributed via Google Forms, consisting of a series of questions or assertions designed for respondents to complete using a Likert scale. For data analysis, the study utilized the SPSS version 26 software to conduct classical assumption tests, multiple linear regression analysis, determination coefficient calculations, and hypothesis testing. Research Finding : The partial findings of the research suggest that brand image factors exert a considerable impact on consumer purchasing choices. In contrast, product quality factors do not appear to significantly impact these choices. On the other hand, price factors are shown to have a considerable impact on purchasing decisions. Nonetheless, when considered together, brand image, product quality, and price factors collectively demonstrate a notable impact on purchasing choices. Theoretical contribution/Originality : This research offers theoretical insights by enhancing the comprehension of how brand image, product quality, and pricing have an effect on purchasing choices regarding Le Minerale bottled drinking water. The investigation emphasizes the simultaneous and partial effects of these three factors on consumer purchasing behavior, particularly among students at Universitas Nusantara PGRI Kediri. Practitionel/Policy implication : This research seeks to make a contribution to the existing body of academic literature. The findings regarding the constructed brand image are anticipated to have an impact on consumer purchasing behavior. While product quality may not directly affect purchasing decisions, it remains crucial to uphold and enhance quality standards. Additionally, competitive pricing plays a significant role in influencing consumer choices. By recognizing the interplay between brand image, product quality, and pricing, Le Minerale can effectively combine these elements to bolster its competitive edge in the bottled water market. Research limitation : This study only focuses on the variables of brand image, product quality, and price on purchasing decisions